2021
DOI: 10.3390/f12111595
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Responses of Larix kaempferi (Lamb.) Carr. Seedling to Short-Term Extreme Climate Events in Summer

Abstract: Extreme climate events such as heat waves, drought, and heavy rainfall are occurring more frequently and are more intense due to ongoing climate change. This study evaluated the early growth performance of one-year-old Larix kaempferi (Lamb.) Carr. seedlings under open-field extreme climate conditions including experimental warming and different precipitation regimes. We recorded the survival rate, root collar diameter, height, biomass, shoot-to-root ratio, and seedling quality index using nine treatments (thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…The root collar diameter and height are the most common indicators in regeneration research (Nissinen et al, 2020). It is widely reported that moderate warming can stimulate plant growth (Noh et al, 2021). In our study, warming (both +2°C and +4°C) increased the root collar diameter of the seedlings (Figure 1A).…”
Section: The Effect Of Climatic Change On Seedling Growthsupporting
confidence: 55%
“…The root collar diameter and height are the most common indicators in regeneration research (Nissinen et al, 2020). It is widely reported that moderate warming can stimulate plant growth (Noh et al, 2021). In our study, warming (both +2°C and +4°C) increased the root collar diameter of the seedlings (Figure 1A).…”
Section: The Effect Of Climatic Change On Seedling Growthsupporting
confidence: 55%